2012
DOI: 10.1177/001440291207900104
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Decoding and Phonological Awareness Interventions for Children with down Syndrome

Abstract: Many children with intellectual disability, including children with Down syndrome, have teachers who are unsure what type of reading instruction is likely to increase outcomes for their students. Effectiveness of two commercially available, evidence-based reading interventions was evaluated through 3 multiple baseline across participants, single-subject research design studies involving 15 children with Down syndrome between the ages of 5 and 13 years. School staff implemented the phonological awareness and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 22 publications
4
49
0
7
Order By: Relevance
“…However, despite the typical deficits in phonological awareness that may present a barrier to children with Down Syndrome benefiting from phonics‐based reading instruction, a number of studies have indicated that using phonics‐based instruction can have a positive effect on the reading skills of children with Down Syndrome (e.g., Lemons & Fuchs, , Lemons et al . ; Al Otaiba & Hosp, ). For example, Cupples and Iacono () investigated the effects of both an analytic, phonics‐based approach and a whole word approach for teaching reading to seven children (five girls and two boys) with Down Syndrome, aged eight to twelve years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the typical deficits in phonological awareness that may present a barrier to children with Down Syndrome benefiting from phonics‐based reading instruction, a number of studies have indicated that using phonics‐based instruction can have a positive effect on the reading skills of children with Down Syndrome (e.g., Lemons & Fuchs, , Lemons et al . ; Al Otaiba & Hosp, ). For example, Cupples and Iacono () investigated the effects of both an analytic, phonics‐based approach and a whole word approach for teaching reading to seven children (five girls and two boys) with Down Syndrome, aged eight to twelve years.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relative strengths in visual processing of individuals with Down Syndrome (Fidler et al, 2009;Visu-Petra et al 2007), and common deficits in auditory processing and memory (e.g., Kernan & Sabsay, 1996;Jarrold and Baddeley, 1997) and phonological awareness (Kay-Raining Bird et al, 2000;Snowling et al, 2002), whole word reading approaches have been particularly recommended for these children (Buckley, 1985;Hodapp & Fidler, 1999;Cossu et al, 1993). However, despite the typical deficits in phonological awareness that may present a barrier to children with Down Syndrome benefiting from phonics-based reading instruction, a number of studies have indicated that using phonics-based instruction can have a positive effect on the reading skills of children with Down Syndrome (e.g., Lemons & Fuchs, 2010, Lemons et al 2012Al Otaiba & Hosp, 2004). For example, Cupples and Iacono (2002) investigated the effects of both an analytic, phonics-based approach and a whole word approach for teaching reading to seven children (five girls and two boys) with Down Syndrome, aged eight to twelve years.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been a number of reviews and meta‐analyses about effective interventions, including a series of IES Practice guides (Gertsten et al., ; Connor, Alberto, Compton, & O'Connor, ) and others describing successful reading interventions (e.g., Al Otaiba, Allor, Ortiz, Greulich, & Wanzek, ; Wanzek & Vaughn, ; Wanzek, Al Otaiba, & Gatlin, ). Several studies have shown that many interventions consistent with the NRP () recommendations are effective for improving the reading outcomes of primary grade students with Autism Spectrum Disorder (ASD) (Whalon, Al Otaiba, & Delano, ), Behavior Disorder (BD) (Rivera, Al Otaiba, & Koorland, 2006), and Intellectual Disability (ID) (Allor, Mathes, Roberts, Cheatham, & Al Otaiba, ; Browder, Wakeman, Spooner, Ahlgrim‐Delzell, & Algozzine, ; Lemons, Mrachko, Kostewicz, & Paterra, ).…”
Section: Special Educators Need To Know How To Implement Data‐based Imentioning
confidence: 99%
“…As described in Lemons, King, et al. (in press), PD for instructors involved four phases of training.…”
Section: Recommendations For Improving Current Professional Developmementioning
confidence: 99%
“…Quite a few intervention studies have targeted early literacy and/or PA with students with DS (Al Otaiba & Hosp, 2004;Baylis & Snowling, 2012;Bourassa, Cleave, & Kay-Raining Bird, 2005;Burgoyne, Duff, Snowling, Buckley, & Hulme, 2013;Burgoyne et al, 2012;Cleave, Kay-Raining Bird, & Bourassa, 2011;Cologon et al, 2011;Cupples & Iacono, 2002;Goetz et al, 2008;Kennedy & Flynn, 2003;Lemons & Fuchs, 2010a;Lemons et al, 2012;van Bysterveldt et al, 2006van Bysterveldt et al, , 2010. These studies are highly heterogeneous with respect to the chronological ages and ability levels of participants, although most focused on older students rather than preschoolers.…”
Section: Introductionmentioning
confidence: 99%